Avoidance behaviour of the shrimp Palaemon varians regarding a contaminant gradient of galaxolide and tonalide in seawater. (October 2019) - Ehiguese, Friday Ojie; Fernandez, María del Carmen Corada; Lara-Martín, Pablo A.; Martín-Díaz, M. Laura; Araújo, Cristiano V.M.
Abstract: The musk fragrances galaxolide (HHCB) and tonalide (AHTN) are compounds of emerging concern that have been found in various environmental compartments. The present study addressed the ability of HHCB and AHTN to elicit the avoidance response in the estuarine shrimp Palaemon varians and to predict the population immediate decline (PID) of P . varians when exposed to HHCB and AHTN by integrating both avoidance (non-forced exposure) and lethality (forced exposure) responses. The avoidance response was tested in a non-forced multi-compartmented static system, in which the shrimps could move freely among the compartments with different concentrations. The shrimps (n = 3 shrimps per compartment/concentration; 18 shrimps per system) were exposed to a gradient (0, 0.005, 0.05, 0.5, 5 and 50 μg/L) of both substances and their positions were checked at every 20 min for a 3 h period. The results from 24-h forced exposure showed no dose-response relationship and the highest percentage mortality was 17% for HHCB at 0.005 and 0.5 μg/L. In the 3-h non-forced exposure to a gradient of HHCB and AHTN, significant concentration-dependent spatial avoidance was observed for both substances. The shrimps avoided the lowest concentration of HHCB and AHTN (0.005 μg/L) by 15% and 16%. The avoidance increased significantly (p < 0.005) to a 61% and 57%, respectively, for the highest concentration (50 μg/L). The population immediate decline was driven by the avoidance behaviour of the shrimps rather than mortality. These results indicated that the aversiveness of HHCB and AHTN might have serious consequences for habitat selection processes by organisms. Graphical abstract: Image 1 Highlights: Shrimps were tested for mortality upon acute exposure to galaxolide and tonalide. Shrimps were tested for avoidance in a multi-compartmented, non-forced system. Avoidance response to a contaminant gradient was concentration-dependent. Population immediate decline is expected to be driven by avoidance behaviour. We recommend integration of both approaches in environmental risk assessments.